The Pruning Effect on the Storage Root Yield and Starch Content of Sweet Potato Clones Planted at Dry Land - Edyson Indawan; Sri Umi Lestari; Nurita Thiasari; Pramono Sasongko (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Sweet potato is a dual-purpose crop, which could produce both food and feed. The vine pruning prior to storage root harvesting was intended to increase the quantity and quality of fresh forage for animal feed. This study aims to evaluate whether periodic pruning can affect the storage root yield and its starch content. This experiment employed split-plot design with two factors and three replications. The first factor as main plot was vine pruning which consisted of four distinct pruning times (four times, three times, twice and once). The second factor as sub-plot was cultivars which consisted of six dual-purpose cultivars and two controls. The storage root yields, vine yields, starch yields and the reduction in storage root yields were observed. The results showed that the vine pruning decreased the storage root yields, with small increases the vine yields. The percentage of the reduction in storage root yields were 4-58%, while the decrease vine yields are relatively inconsistent. The starch yield of the cultivars with one pruning time were in the range of 2.34-6.67 ton ha-1. On the contrary, the three times pruning or more since 80 days after transplanted can reduce the starch yields for more than 50%. The slight increase in vines yield due to pruning was followed by the decrease in storage root yields and starch content of the sweet potato.